2021
DOI: 10.1177/21501327211018936
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Female Out-of-School Adolescents in Accessing and Utilizing Sexual and Reproductive Health Service: A Qualitative Exploratory Study in Southwest, Ethiopia

Abstract: Introduction Due to the limited access to sexual and reproductive health service, out-of-school-adolescents become at a higher risk for early marriage, early pregnancy early parenthood, and poor health outcomes over their life course. Hence, the aim of this study was to explore the challenges faced by female out-of-school adolescents in accessing sexual and reproductive health service in Bench-Sheko zone. Methods A community-based qualitative exploratory study was carried out from November 01/2020 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…This finding is consistent with other findings in Ethiopia. 3,16 Similar to this study finding, the finding of a study conducted in DR Congo also shows stigma discouraged adolescents to access and utilized sexual and reproductive health services. 25 Another qualitative study in Tanzanian found that adolescents discouraged seeking SRH services due to community stigma.…”
Section: Dovepresssupporting
confidence: 84%
See 3 more Smart Citations
“…This finding is consistent with other findings in Ethiopia. 3,16 Similar to this study finding, the finding of a study conducted in DR Congo also shows stigma discouraged adolescents to access and utilized sexual and reproductive health services. 25 Another qualitative study in Tanzanian found that adolescents discouraged seeking SRH services due to community stigma.…”
Section: Dovepresssupporting
confidence: 84%
“…Studies conducted in southern Ethiopia and southwest Ethiopia also support this study finding. 3 , 16 A qualitative study conducted in South Africa also shows that insufficient SRH skills and shortage of time to provide the necessary care hinder the provision of adequate SRH services to adolescents. 4 This study finding implies that health system barrier further contributes to the unfriendliness of the services environment to access and utilization of sexual and reproductive health services by unmarried adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some countries or communities, introducing SRH services for adolescents in their homes could be a challenge. Discussion of topics pertaining to SRH has been mentioned to be restricted in some homes and communities [ 47 , 48 ] because it is unacceptable or frowned upon. Adolescents who are not exposed to the topic of SRH during this stage of their lives are likely to be naïve about the topic when they become adults.…”
Section: Discussionmentioning
confidence: 99%